Novel roles of the multi-functional CCR4-NOT complex in post-transcriptional regulation - Inada, Toshifumi; Makino, Shiho (Frontiers in Genetics, 2014)
The CCR4-NOT complex is a highly conserved specific gene silencer that also serves more general post-transcriptional functions. Specific regulatory proteins including the miRNA-induced silencing complex and its associated proteins, bind to 3’-UTR elements of mRNA and recruit the CCR4-NOT complex thereby promoting poly(A) shortening and repressing translation and/or mRNA degradation. Recent studies have shown that the CCR4-NOT complex that is tethered to mRNA by such regulator(s) represses translation and facilitates mRNA decay independent of a poly(A) tail and its shortening. In addition to deadenylase activity, the CCR4-NOT complex also has an E3 ubiquitin ligase activity and is involved in a novel protein quality control system, i.e., co-translational proteasomal-degradation of aberrant proteins. In this review, we describe recent progress in elucidation of novel roles of the multi-functional complex CCR4-NOT in post-transcriptional regulation.